Control strategies for citrus postharvest diseases - Auret, Erika Elizabeth (2013)
Please read the abstract in the section 06resume.pdf of this document === Dissertation (MSc (Plant Pathology))--University of Pretoria, 2007. === Microbiology and Plant Pathology === unrestricted